2007
DOI: 10.1070/sm2007v198n11abeh003901
|View full text |Cite
|
Sign up to set email alerts
|

The degree of $ \mathbb Q$-Fano threefolds

Abstract: We consider B-type D-branes in the Gepner model consisting of two minimal models at k = 2. This Gepner model is mirror to a torus theory. We establish the dictionary identifying the B-type D-branes of the Gepner model with A-type Neumann and Dirichlet branes on the torus.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…In [Nam97], Namikawa showed that every terminal Gorenstein Fano 3-fold Y can be deformed to a smooth Fano 3-fold, in particular we have Vol(−K Y ) ≤ 64. Moreover Prokhorov proved that the degree of a Q-factorial terminal non-Gorenstein Fano 3-fold of Picard rank one is bounded by 125/2 ( [Pro07]). All together, we have Vol(−K X ′ ) ≤ 64.…”
Section: Explicit Fujita-type Statementsmentioning
confidence: 99%
“…In [Nam97], Namikawa showed that every terminal Gorenstein Fano 3-fold Y can be deformed to a smooth Fano 3-fold, in particular we have Vol(−K Y ) ≤ 64. Moreover Prokhorov proved that the degree of a Q-factorial terminal non-Gorenstein Fano 3-fold of Picard rank one is bounded by 125/2 ( [Pro07]). All together, we have Vol(−K X ′ ) ≤ 64.…”
Section: Explicit Fujita-type Statementsmentioning
confidence: 99%
“…In the third row we indicate the number of candidates which do not occur as Q-Fano threefolds. This is according to this paper and [Pro07]. The fourth row shows the number baskets for which we know examples of Q-Fano threefolds.…”
Section: Introductionmentioning
confidence: 88%
“…This work is a sequel to our previous papers [Pro07], [Pro10]. Recall that a three-dimensional projective variety X is called Q-Fano threefold if it has only terminal Q-factorial singularities, Pic(X) ≃ Z, and its anticanonical divisor −K X is ample.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In fact, Kawamata's proof implies that the possible "candidate" Q-Fano 3-folds can be listed, although the volume of computation makes computer searches inevitable. This method was used in [Suz04], [BS07a], [BS07b], [Pro07], [Pro10b], [Pro10c]. See [GRDB] for explicit lists.…”
Section: Computer Search For Q-fano 3-foldsmentioning
confidence: 99%